Towards democratised psychiatry: building metacommunities for inclusive and equitable global mental health - Yansen Alberth Reba; M. Zaenul Muttaqin; Yovian Yustiko Prasetya (BJPsych International)
Through their study, George Ikkos & Nick Bouras reveal that the responsibilities of the psychiatric community are increasingly complex, especially amid the onslaught of globalisation and the confines of neoliberalism. ‘Metacommunity’ in this context refers not only to the history of psychiatrists but their role in strengthening and influencing mental health policies. A number of challenges continue to emerge in the public sphere, highlighting the need for psychiatry to adapt to society's evolving demands for inclusivity, equity and ethical governance. These challenges emphasise the importance of shaping the future of psychiatry that is responsive to the complexities of mental health care and aligned with democratic principles that prioritise transparency and social accountability. We have added several aspects that could complement psychiatrists' future theory and practice, including a more collaborative and evidence-based approach to dealing with increasingly complex mental health issues.